Необхідність розроблення концепції безпекового середовища на прикладі МВС України: нормативно-кримінологічні та духовно-ціннісні аспекти - Погрібний, С. О.; Pogribnyi, S. O.; Кріцак, І. В.; Kritsak, I. V.; Денищук, Д. Є.; Denyshchuk, D. Ye.; Іван Кріцак; Денис Денищук (Нове українське право. – 2022. – Вип. 4. – С. 95-103, 2022)
Розглянуто проблему нормативно-законодавчої бази нинішнього безпекового середовища, актуалізовано його роль з духовно-ціннісних міркувань, формування високих рівнів правової психології та правової ідеології громадян, з вибудовування відповідного концепту загальнонаціонального рівня, а саме: «воля», «цінності», «культура», «безпека». Порушено питання подолання негативного безпекового середовища крізь призму нинішніх криміногенних станів, ситуацій та обстановки. Узагальнено міжнародний досвід ефективних правоохоронних та оборонних практик і взаємодій. Наголошено, що серед генеральних напрямів, які слід розробляти у Концепції безпекового середовища, запропоновано кібербезпеку та психологічний (духовно-ціннісний) безпековий складник.

The authors raise important issues of normative-legal framework the current security environment, his role is actualized with spiritual and value considerations, formation of high levels legal psychology and legal ideology of citizens, from the construction of the corresponding concept national level, namely: “will”, “values”, “culture”, “security”. A significant role in these processes belongs to the Ministry of Internal Affairs of Ukraine (in particular the National Police of Ukraine, as the largest law enforcement agency of our country, when from police structures world and national levels, their effective (fruitful) work and providing services and quality service to its people, jointly, in interaction with citizens and state bodies success and stability will depend stability of order in the state (on it internal, invisible front), as well as achieving victories on the front lines in the difficult conditions of the Russian-Ukrainian war.Issues of overcoming the negative are raised security environment through the prism of current ones’ criminogenic states, situations and circumstances; the international experience of effective ones is summarized law enforcement and defense practices and interactions. It is noted that most often in scientific articles are about the security environment in the field of economy, health care, education and culture. At the same time, it should be considered from the positions various interpretations (in particular interdisciplinary-scientometric) that will help to see the comprehensiveness of importance spheres of security in the most diverse spectrums preservation of human life and health, its normal existence and aspiration to high truths. Among the general directions that should be developed in Security environment concepts is offered cyber security and psychological (spiritual-value) security components (given that the sociological and psychological school Kharkiv region is one of the most powerful in Ukraine).It is emphasized that the processing of this problem requires a great effort of many searches and analysis in order to constantly conceptualize threats and challenges, which poses every lived day in conditions of unstable situations, new states of war, when the entire system of international security regarding building peace and stability blown up to the ground and humanity reached the extreme point of its boiling point, when exercises are conducted on the use of nuclear weapons.

Рассмотрена проблема нормативно-законодательной базы нынешней среды безопасности, актуализирована ее роль по духовно-ценностным соображениям, формированию высоких уровней правовой психологии и правовой идеологии граждан, по выстраиванию соответствующего концепта общенационального уровня, а именно: «воля», «ценности», «культура» , «безопасность». Поднят вопрос преодоления негативной среды безопасности сквозь призму нынешних криминогенных состояний, ситуаций и обстановки. Обобщен международный опыт эффективных правоохранительных и оборонных практик и взаимодействий. Отмечено, что среди генеральных направлений, которые следует разрабатывать в Концепции среды безопасности, предложены кибербезопасность и психологическая (духовно-ценностная) составляющая безопасности.
The need to develop a concept safe environment on the example of the Ministry of Internal Affairs of Ukraine: normative-criminological and spiritual-value aspects
Погрібний, С. О. Необхідність розроблення концепції безпекового середовища на прикладі МВС України: нормативно-кримінологічні та духовно-ціннісні аспекти / Погрібний Сергій Олексійович, Кріцак Іван Васильович, Денищук Денис Євгенійович // Нове українське право. – 2022. – Вип. 4. – С. 95-103. - DOI: https://doi.org/10.51989/NUL.2022.4.14.
Keywords: Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; безпекове середовище; safe environment; среда безопасности; національна безпека; national security; национальная безопасность; правоохоронні органи; law enforcement agencies; правоохранительные органы; російсько-українська війна; Russian-Ukrainian war; русско-украинская война; зарубіжний досвід; foreign experience; зарубежный опыт; правове забезпечення; legal support; правовое обеспечение; МВС України